BIMBINGAN AKHLAK PADA SANTRI MAGRIB MENGAJI MELALUI PENDEKATAN KAJIAN KITAB TA’LIMUL MUTA’ALIM - Muhammad Saepul Ulum (Jurnal Bimbingan Penyuluhan Islam, 2021)
Children are a gift entrusted by God to parents to protect their safety both in the world and in the hereafter. The care that is given to children is of course not arbitrary, it requires complete love and full responsibility to guide them so that they are safe and always be in their nature. Therefore, parents are obliged to pay attention to all aspects of child development, starting based on the child's welfare, health & education. Not a few of the parents who send their children to madrasah on the grounds that children receive deeper religious guidance. There is a hope that parents make their children as students so that the knowledge of religion can be a foundation for creating good morals, so that children will have powerful guidelines for returning all their affairs according to Islamic principles. This study aims to find out the self-understanding of students through studying the Ta'limul Muta'alim book, self-direction of the students through studying the Ta'limul Muta'alim book, and self-actualizing through the study of the Ta'limul Muta'alim book. Moral guidance is an effort to guide a person in a direction that is beneficial to his life through self-understanding, and self-direction in future actualization through the system of monotheism to Allah SWT which is manifested in a commendable form of attitude. Because the moral aspect discusses behavior, deeds and courtesy, both to Allah SWT and to fellow humans. Including the obligations that must be carried out by students who must be cultivated in order to achieve perfect morals. The method used in this research is descriptive qualitative, which describes the facts found in the field using data collection techniques through observation, interviews, & documentation. Using data validity through credibility, transferbility, dependability & confirmability tests. The results of the study illustrate that 1) the self-understanding of the magrib santri to recite through the study of the book Ta'limul Muta'alim the santri are introduced to the potential good morals that they have in Allah SWT, Morals in teachers, other students and morals in science; 2) Self-direction of students through starting with straightening the intention because of Allah SWT, practicing patience as well as keistiqomahan, & tawakal in Allah SWT; 3) Self-actualization through the study of the Book of Ta'limul Muta'alim can be seen from the achievement of indicators regarding the students' self-understanding of the moral potential they have. In this study, the students showed good and sufficient self-understanding and direction.